2014
DOI: 10.1109/tpwrd.2014.2311112
|View full text |Cite
|
Sign up to set email alerts
|

Overvoltages due to Synchronous Tripping of Plug-in Electric-Vehicle Chargers Following Voltage Dips

Abstract: Plug-in electric vehicle (PEV) charging equipment incorporates protection that ensures that grid disturbances do not damage the charger or vehicle. When the grid voltage sags below 80% of nominal, undervoltage protection is likely to disconnect the charging load from the grid. Most PEV charging will occur overnight, when non-PEV load is at a minimum. This paper argues that PEV voltage-sag response, when synchronized across large numbers of PEVs, could result in the loss of a significant proportion of the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Accordingly, it can be concluded that the likely impact of voltage sags and short interruptions on an increasing share of electronic and power-electronic-based electrical equipment -if no action is taken by OFGEM or GB DNOs -will be greater. For example, according to [24], plug-in EV voltage-sag response, when synchronised across large numbers of plug-in EVs, could result in the loss of a significant proportion of the total load, which could result in unacceptably high voltages once the initiating voltage sag event is cleared. Similar voltage-sag-, swell-or interruption-events could lead to a trip/malfunction of a combination of varying levels of load-generation that could further trigger a voltage/frequency stability event.…”
Section: Impact Of Electricity Supply Disturbances On Factory Manufacmentioning
confidence: 99%
“…Accordingly, it can be concluded that the likely impact of voltage sags and short interruptions on an increasing share of electronic and power-electronic-based electrical equipment -if no action is taken by OFGEM or GB DNOs -will be greater. For example, according to [24], plug-in EV voltage-sag response, when synchronised across large numbers of plug-in EVs, could result in the loss of a significant proportion of the total load, which could result in unacceptably high voltages once the initiating voltage sag event is cleared. Similar voltage-sag-, swell-or interruption-events could lead to a trip/malfunction of a combination of varying levels of load-generation that could further trigger a voltage/frequency stability event.…”
Section: Impact Of Electricity Supply Disturbances On Factory Manufacmentioning
confidence: 99%
“…In a recent study, an analysis tool was presented that determines a critical EV charging load based on the non-EV load on a distribution feeder (Kundu and Hiskens 2014). As the EV charging load fraction increases the likelihood of postdisturbance voltage rise increases.…”
Section: Grid Stability With Evsmentioning
confidence: 99%
“…To model the effect of EV chargers tripping on the voltage profile of the transmission grid, a model of the transmission grid needs to be considered along with a model for the residential feeder. In the research reported in this paper, the conventional IEEE 39-bus system (IEEE 10 Generator 39 bus system model) is considered as the transmission grid, while a modified IEEE 34-node system (Kundu and Hiskens 2014) is considered as the residential feeder; see the "Supplemental Data" section for diagrams and further details of those systems. In the analyzed case, a fault in the transmission grid causes a voltage sag impacting the residential feeder.…”
Section: Grid Stability With Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the loads can present some degree of intelligence used to adapt its power demand depending on local measures or remote commands. In this sense, a challenging and attractive load form is the plug-in electric vehicle charged from residential distribution feeders, which can be used also to store energy and other ancillary purposes [2,3]. Thanks to the advances in power electronics, high performance power converters are commonly used as interface between the generation sources and the grid.…”
Section: Introductionmentioning
confidence: 99%